The Vibrodiagnostics of Damaged Gears of Planetary Gearboxes - Lubos Kucera; Tomas Gajdosik; Jan Bucala (Communications - Scientific letters of the University of Zilina, 2014)
This article deals with description of a diagnostic device used at the Department of Design and Machine Elements at the University of Zilina which has been built in order to measure, diagnose and evaluate gearbox faults by vibrodiagnostics. The article describes methods and damage creation process for tested gearboxes. Evaluation of different faults is also processed in this article as well as description of comparative measurements between real and artificially created pitting. Comparison of all measured data with SPM methods is also included.